Have dragon an edible cactus fruit - Shankaraswamy, J; Neelavathi, R (Indian Horticulture, 2015)
Like climbing fruit crops, supporting, training and pruning are essential for commercial cultivation of cactus. Since fruits have health promoting phytochemicals and low calories, these can be recommended to diabetic patients. Due to the presence of antioxidant pigments particularly betalains, fruits can be exploited for commercial production of processed products and natural colourants.